2002
DOI: 10.1210/jc.2001-020243
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Central Precocious Puberty by Subcutaneous Injections of Leuprorelin 3-Month Depot (11.25 mg)

Abstract: Depot GnRH agonists are widely used for the treatment of precocious puberty. Leuprorelin 3-month depot is currently used in adults but has not been evaluated in children. We evaluated the efficacy of this new formulation (11.25 mg every 3 months), for the suppression of gonadotropic activation and pubertal signs in children with central precocious puberty. We included 44 children (40 girls) with early-onset pubertal development in a 6-month open trial. The inclusion criteria were clinical pubertal development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 28 publications
6
52
1
8
Order By: Relevance
“…They also confirm the need for precise monitoring of gonadotropin secretion in children treated with GnRH agonists. These results confirm the efficacy, tolerability and acceptability of the 3-month formulations of GnRH agonists in children (16).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…They also confirm the need for precise monitoring of gonadotropin secretion in children treated with GnRH agonists. These results confirm the efficacy, tolerability and acceptability of the 3-month formulations of GnRH agonists in children (16).…”
Section: Discussionsupporting
confidence: 79%
“…Subcutaneous intolerance to depot GnRH agonists has been reported and is mostly due to reaction to the lactide-coglycolide polymer (9,11,16,26,27). In the present study, mild-to-moderate local reactions at the injection site were reported in 8% of the children, and injection pain in only 3%.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…Nos prontuários das 31 pacientes restantes (17,7%) foram relatados antecedentes familiais de PP (mãe em 14 casos). A menarca materna foi informada em 159 casos, tendo ocorrido aos 12,1 ± 0,1anos (8,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)0).…”
Section: Características Epidemiológicasunclassified